Pengaruh Lingkungan Kerja Fisik Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Kantor Kecamatan Pinang Kota Tangerang - Syafira Amelia; Vega Anismadiyah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to determine the effect of work environment and career development on employee performance, both partially and simultaneously, at the Pinang District Office, Tangerang City. The method used is a quantitative method. The sampling technique used was saturated sampling with a sample of 75 respondents. Data were collected through observation and questionnaires. The results of multiple linear regression produced the equation Y = 4.863 + 0.260 X₁ + 0.184 X₂, indicating that the work environment and career development have a positive effect on employee performance. The coefficient of determination (R- Square) of 37.1% indicates that 37.1% of the variation in employee performance is explained by work environment and career development. In the partial test (t- test), the work environment (X₁) has a Tcount of 4.888> Ttable 1.993 with a significance of 0.000, which means that work discipline has a significant effect on employee performance. Career development (X₂) is also significant with a Tcount of 5.397> Ttable 1.990 and a significance of 0.000. The simultaneous test (F test) shows a calculated F value of 14.315 > Ftable 3.12 with a significance of 0.000, which means that the work environment and career development simultaneously have a significant effect on employee performance at the Pinang District Office, Tangerang City